2023
DOI: 10.1109/tnnls.2020.3006738
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Dynamic Time Warping Kernels for Co-Evolving Financial Time Series Analysis

Abstract: Network representations are powerful tools to modelling the dynamic time-varying financial complex systems consisting of multiple co-evolving financial time series, e.g., stock prices, etc. In this work, we develop a novel framework to compute the kernel-based similarity measure between dynamic time-varying financial networks. Specifically, we explore whether the proposed kernel can be employed to understand the structural evolution of the financial networks with time associated with standard kernel machines. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The studies in natural language processing (NLP) [193]- [195] have demonstrated that GMs can process natural language and have were taken around each of the two events. [191]. achieved much better performance than the conventional NLP models.…”
Section: Extracting Graphic Gcsmentioning
confidence: 95%
See 3 more Smart Citations
“…The studies in natural language processing (NLP) [193]- [195] have demonstrated that GMs can process natural language and have were taken around each of the two events. [191]. achieved much better performance than the conventional NLP models.…”
Section: Extracting Graphic Gcsmentioning
confidence: 95%
“…Another example is about studying co-evolving financial time-serious problems from GMs. In [191], Bai et al proposed a tool, called EDTWK (Entropic Dynamic Time Warping Kernels), for time-varying financial networks. They computed the commute time matrix on each of the network structures for satisfying a GC as "the financial crises are usually caused by a set of the most mutually correlated stocks while having less uncertainty [191], [192]".…”
Section: Extracting Graphic Gcsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Feng et al [36] created the relations between every pair (two industries) based on a knowledge base to predict stock trends. Graph kernels were also able to play an important role in the financial time series analysis by associating it with the classical dynamic time warping framework [37,38]. And, in the multimedia field, Cucurull et al [39] promoted the fashion compatibility prediction problem using a graph convolutional network that learned to generate product embeddings conditioned on context.…”
Section: Graph Neural Networkmentioning
confidence: 99%